2015
DOI: 10.1038/nature14234
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine-dependent RNA structural switches regulate RNA–protein interactions

Abstract: RNA-binding proteins control many aspects of cellular biology through binding single-stranded RNA binding motifs (RBM)1-3. However, RBMs can be buried within their local RNA structures4-7, thus inhibiting RNA-protein interactions. N6-methyladenosine (m6A), the most abundant and dynamic internal modification in eukaryotic messenger RNA8-19, can be selectively recognized by the YTHDF2 protein to affect the stability of cytoplasmic mRNAs15, but how m6A achieves wide-ranging physiological significance needs furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
1,691
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,649 publications
(1,740 citation statements)
references
References 45 publications
39
1,691
2
8
Order By: Relevance
“…The identity of any of the other proteins that act together with METTL3 remained unknown until it was shown in Arabidopsis that FIP37 (FKBP12 INTERACTING PROTEIN 37) was a partner protein of MTA (the homologue of METTL3) (Zhong et al ., 2008; Shen et al ., 2016). Following this initial discovery, the homologues of FIP37, S. cerevisiae MUM2 (Muddled Meiosis 2), and mammalian WTAP (Wilms tumour 1 associated protein), were shown to interact with METTL3 (MTA) orthologues and to be required for mRNA methylation in their respective model organisms (Agarwala et al ., 2012; Ping et al ., 2014; Wang et al ., 2014b; Liu et al ., 2015). More recently, another human methylase, METTL14, phylogenetically related to METTL3 (Bujnicki et al ., 2002), was shown to form a complex with METTL3 and WTAP, and to be required also for m 6 A formation (Ping et al ., 2014; Wang et al ., 2014b; Liu et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The identity of any of the other proteins that act together with METTL3 remained unknown until it was shown in Arabidopsis that FIP37 (FKBP12 INTERACTING PROTEIN 37) was a partner protein of MTA (the homologue of METTL3) (Zhong et al ., 2008; Shen et al ., 2016). Following this initial discovery, the homologues of FIP37, S. cerevisiae MUM2 (Muddled Meiosis 2), and mammalian WTAP (Wilms tumour 1 associated protein), were shown to interact with METTL3 (MTA) orthologues and to be required for mRNA methylation in their respective model organisms (Agarwala et al ., 2012; Ping et al ., 2014; Wang et al ., 2014b; Liu et al ., 2015). More recently, another human methylase, METTL14, phylogenetically related to METTL3 (Bujnicki et al ., 2002), was shown to form a complex with METTL3 and WTAP, and to be required also for m 6 A formation (Ping et al ., 2014; Wang et al ., 2014b; Liu et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…HNRNPC may thus interact with the pre-rRNA before cleavage of the internal transcribed spacer 1 (ITS1) that separates 18S and 28S rRNA. A recent study revealed that RNA binding of HNRNPC is enhanced upon addition of m 6 A modifications (Liu et al 2015), and it is possible that HNRNPC interacts with rRNA in an m 6 A-dependent manner. Furthermore, HNRNPD was identified in the same study as being involved in large ribosomal subunit maturation (Henras et al 2015).…”
Section: Identification Of Previously Unrecognized Ribosomal Rbpsmentioning
confidence: 99%
“…Based on this model, it is plausible that pre-mRNA m 6 A marks may modulate local binding of regulators of the splicing machinery. To address this possibility, we compiled a list of RNA-binding proteins that differentially bind methylated RNA (Alarcón et al, 2015b;Edupuganti et al, 2017;Liu et al, 2015). We then systematically analyzed the distribution of binding sites of each RBP (derived from CLIP-seq data and known RBP binding motifs, 33 RBPs were included in this analysis) to determine if each candidate RBP binds to introns (and their flanking exons) that are also bound by TARBP2 and/or contain m6A marks.…”
Section: Tarbp2-dependent Mmentioning
confidence: 99%
“…The prevalent internal RNA modification mark N(6)-methyladenosine (m 6 A) has been reported to play a role in regulating most facets of the RNA life cycle, including regulation of pre-mRNA splicing, mRNA stability, and mRNA translation (Lin et al, 2016;Liu et al, 2015;Wang et al, 2015Wang et al, , 2014Xiao et al, 2016;Zhao et al, 2014). Recently, work by us (Alarcón et al, 2015) and others (Ke et al, 2017;Knuckles et al, 2017) has established that m 6 A marks are deposited in the nucleus and are proposed to function in many nuclear regulatory processes, including microRNA and messenger RNA processing.…”
Section: Introductionmentioning
confidence: 99%